Pengaruh Kompetensi Karir terhadap Kemampuan Kerja yang Dirasakan, dengan Dimediasi oleh Kesuksesan Karir dan Dimediator oleh Kejutan Karir pada Mahasiswa Politeknik Penerbangan - Musri Kona; Rifqi Raza Bunahri (Dinasti Review, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the effect of career competence on perceived employability, mediated by career success and mediated by career shock in aviation polytechnic students, a study of human resources literature. The results of this literature review article are: 1) career competence influences perceived work ability; 2) career success mediates the relationship between career competence and perceived ability; and 3) Career shock moderates the relationship between career competence and perceived ability.